Achievement Motivation of Undergraduates Divided by Sport Activity - Pavel Smela; Petra Pacesova; Stanislav Kracek; Klaudia Kukurova; Nina Halacova (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
This paper strives to contribute to performance motivation research and to point out diff erences in achievement motivation among college students in terms of sports activities. The research sample was comprised of 248 college students (men: n=141, 22.40±1.62 years of age; women: n=107, 21.78±1.49 years of age) from Bratislava. The respondents were divided into 3 groups according to frequency of sports activities: college students who didn't engage in any sports activities (non-active respondents), college students who engaged in sports activities 1 to 2 times a week (moderately active respondents), and those who engaged in sports activities 3 or more times a week (highly active respondents). A standardized DMV questionnaire consisting of 52 items was used as the research tool. The Kolmogorov-Smirnov test was used to assess the normality of data and the Kruskal-Wallis test and MannWhitney tests were used to test the signifi cance of the diff erences between independent choices. The coeffi cient η2 , expressed the eff ect of the independent variable (sport activity) on the dependent variable (achievement motivation). The degree of dependence between the two of the groups of features was expressed by means of the coeffi cient r. The results revealed signifi cant (p≤0.001) diff erences in all three performance motivation dimensions. The performance motivation of the highly active respondentswas signifi cantly (p=0.000) higher compared to that of the moderately active respondents. Also, when compared with the non-active respondents, the level of performance motivation was signifi cantly (p=0.000) higher among the highly active respondents. Performance motivation and performance-supporting anxiety increases with the frequency of sports activities; on the contrary, performance-hindering anxiety decreases with the frequency of sports activities. Hence, our results testify to the fact that sport activity is one of the determinants for increased performance motivation.